Gene-editing techniques and their applications in livestock and beyond - Tae Sub Park (Animal Bioscience, 2023)
Genetic modification enables modification of target genes or genome structure in livestock and experimental animals. These technologies have not only advanced bioscience but also improved agricultural productivity. To introduce a foreign transgene, the piggyBac transposon element/transposase system could be used for production of transgenic animals and specific target protein-expressing animal cells. In addition, the clustered regularly interspaced short palindromic repeat-CRISPR associated protein 9 (CRISPR-Cas9) system have been utilized to generate chickens with knockout of G0/G1 switch gene 2 (G0S2) and myostatin, which are related to lipid deposition and muscle growth, respectively. These experimental chickens could be the invaluable genetic resources to investigate the regulatory pathways and mechanisms of improvement of economic traits such as fat quantity and growth. The gene-edited animals could also be applicable to the livestock industry.